Um banquete de ideias: o juízo crítico na restauração do afresco de Andrea Mantegna - Anamaria Ruegger Almeida Neves (2010)
On my research, I looked for a balance between Thought and Techno-science. As an art conservator, I am worried about the decisions for restoration treatments, mainly the pictorial ones. I believe that decision taking needs to be preceded and accompanied by a critical judgment, which is developed not only through discussions and debates with partner meetings, but also, studying various knowledge areas. The art works are represented on our culture by their Aesthetics and History, as witnesses of their time and place. I am aware that technology development is a hallmark of the present age and, obviously, its utilization on Conservation is very important because it yields new technical resources. On the other hand, I ask if theory and critical judgment are being applied during the decision taking or, in other words, during the moment when the best treatment is defined. Through the Art of Memory, Iwalked on ways that introduced me to the conservation theorists, to the philosophers, to the frescoes treatises and also to the physicists and mathematicians. I selected, as an Agent Image to explore my thoughts, the restoration via Computer-based Recomposition process, developed by the Physics Department of the Padua University in Italy, for the AndreaMantegna frescoes painted on the Ovetari Chapel in the Eremite Church in the same city. I looked for a relationship between different ideas, presenting new and old views in the search for a theoretical support for the decisions related to pictorial treatments which consider the Aesthetical meanings on art works. I reinforce the necessity of understanding the art work on all concepts: historic, artistic and cultural, and also its place on time and location, choosing decisions for each specific situation and moment. I looked for the dialog with other wallpainting restorations experiences and I also present another Computer-based Recomposition restoration process developed and carried out at the Polytechnique University of Valencia in Spain. Without intentions to compare methods or results, but understand the Visual Pedagogy that results of a restored art work.